Three-dimensional multipotent progenitor cell aggregates for expansion, osteogenic differentiation and “in vivo” tracing with AAV vector serotype 6 - Ferreira, Joäo R. (2012)
Multipotent adult progenitor cells (MAPC) are bone marrow-derived stem cells with a high growth rate suitable for therapeutical applications as three-dimensional (3D) aggregates. Combined applications of osteogenically differentiated MAPC (OD-MAPC) aggregates and adeno-associated viral vectors (AAV) in bone bioengineering are still deferred until information regarding expansion technologies, osteogenic potential, and AAV cytotoxicity and transduction efficiency is better understood. In this study, we tested whether self-complementary AAV (scAAV) can potentially be used as a gene delivery system in a OD-MAPC-based “in vivo” bone formation model in the craniofacial region. Both expansion of rat MAPC (rMAPC) and osteogenic differentiation with dexamethasone were also tested in 3D aggregate culture systems “in vitro” and “vivo”. Rat MAPCs (rMAPCs) grew as undifferentiated aggregates for 4 days with a population doubling time of 37h. After expansion, constant levels of Oct4 transcripts, and Oct4 and CD31 surface markers were observed, which constitute a hallmark of rMAPCs undifferentiated stage. Dexamethasone effectively mediated rMAPC osteogenic differentiation by inducing the formation of a mineralized collagen type I network, and facilitated the activation of the wnt/β-catenin, a crucial pathway in skeletal development. To investigate the genetic modification of rMAPCs grown as 3D aggregates prior to implantation, scAAV serotypes 2, 3, and 6 were evaluated. scAAV6 packaged with the enhanced green fluorescent protein expression cassette efficiently mediated long-term transduction (10 days) “in vitro” and “vivo”. The reporter transduction event allowed the tracing of OD-rMAPC (induced by dexamethasone) aggregates following OD-rMAPC transfer into a macro-porous hydroxyapatite scaffold implanted in a rat calvaria model. Furthermore, the scAAV6-transduced OD-rMAPC generated a bone-like matrix with a collagenous matrix rich in bone specific proteins (osteocalcin and osteopontin) in the scaffold macro-pores 10 days post-implantation. Newly formed bone was also observed in the interface between native bone and scaffold. The collective work supports future bone tissue engineering applications of 3D MAPC cultures for expansion, bone formation, and the ability to genetically alter these cells using scAAV vectors.